Teori ACTORS dalam Pemberdayaan Masyarakat - Maani, Karjuni Dt. (Jurnal Demokrasi, 2011)
By using the concept of empowerment that are offered within the framework of the theory of "ACTORS", then the changes that will result is a change has been planned, because the input to be used in the change was anticipated early on so that the output will be produced capable of optimally efficient. The study of the management of community development using the framework of "ACTORS" will be able to raise awareness, authority, confidence and competence, trust, oppurtinities, responsibilities, support, initiative, and creativity to change the situation towards the power in which communities have self-respect, self confident, and self relience, so they have the knowledge and understanding for self-empowerment on an ongoing basis. Kata Kunci: empowerment, authority, confidence and competence, trust, oppurtinities, responsibilities, support